Self-reported symptoms and risk factors for digital ischaemia among international world-class beach volleyball players - Van De Pol, D.; Alaeikhanehshir, S.; Maas, M.; Kuijer, P. P. F. M. (Journal of Sports Sciences, 2016)
The prevalence of ischaemia-related symptoms is remarkably high among elite indoor volleyball players. Since the exposure to sport-specific demands may be higher in beach volleyball compared to indoor volleyball, the aim of this study was to assess the prevalence of ischaemia-related symptoms and associated risk factors among world-class beach volleyball players. Therefore, a questionnaire survey was performed among beach volleyball players active during the 2013 Grand Slam Beach Volleyball in the Netherlands. In total, 60 of the 128 beach volleyball players (47%) participated: 26 males and 34 females from 17 countries. The self-reported prevalence of cold or blue or pale digits in the dominant hand during or immediately after practice or competition was 38% (n = 23). Two risk factors were independently associated with symptoms of blue or pale digits: more than 14 years playing volleyball (odds ratio (OR) 4.42, 90% confidence interval (90% CI) 1.30-15.07) and sex (female) (OR 4.62, 90% CI 1.15-18.57). In conclusion, the prevalence of symptoms associated with digital ischaemia is high among international world-class beach volleyball players. Female sex and the length of the volleyball career were independently associated with an increased risk of ischaemia-related symptoms. The high prevalence of these seemingly innocuous symptoms and possible associated risk factors warrant regular monitoring since early detection can potentially prevent thromboembolic complications and irreversible tissue damage.